Combining nano-differential scanning fluorimetry and microscale thermophoresis to investigate VDAC1 interaction with small molecules - Hubert Gorny; Angélique Mularoni; Jean-Guy Delcros; Céline Freton; Jordane Preto; Isabelle Krimm (Taylor & Francis Group, 2023)
The mitochondrial voltage-dependent anion channel 1 (VDAC1) plays a central role in metabolism and apoptosis, which makes it a promising therapeutic target. Nevertheless, molecular mechanisms governing VDAC1 functioning remain unclear. Small-molecule ligands specifically interacting with the channel provide an attractive way of exploring its structure-function relationships and can possibly be used as founding stones for future drug-candidates. While around 30 VDAC1 ligands have been identified over the years, various techniques have been used by research teams, making a fair and direct comparison between compounds impossible. To tackle this issue, we performed ligand-binding assays on a representative set of seventeen known VDAC1 ligands using nano-differential scanning fluorimetry and microscale thermophoresis. While all the compounds have been confirmed as VDAC1 ligands by at least one method, combining both technologies lead to the selection of four molecules (cannabidiol, curcumin, DIDS and VBIT4) as chemical starting points for future design of VDAC1 selective ligands.